Counseling for Prenatal Congenital Heart Disease—Recommendations Based on Empirical Assessment of Counseling Success - Kovacevic, Alexander; Simmelbauer, Andreas; Starystach, Sebastian; Elsässer, Michael; Müller, Andreas; Bär, Stefan; Gorenflo, Matthias (Frontiers in Pediatrics, 2020)
Objectives Empirical assessment of parental needs and affecting factors for counselling success after prenatal diagnosis of congenital heart disease (CHD). Methods Counselling success after fetal diagnosis of CHD was assessed by a validated standardized questionnaire. The dependent variable “Effective Counselling” was measured in five created analytical dimensions (1. “Transfer of Medical Knowledge-ToMK”; 2. “Trust in Medical Staff-TiMS”; 3. “Transparency Regarding the Treatment Process-TrtTP”; 4. “Coping Resources-CR”; 5. “Perceived Situational Control-PSC”). Analyses were conducted with regard to influencing factors and correlations. Results 61 individuals (n=40 female, n=21 male) were interviewed in a tertiary medical care center. Median gestational age at first parental counselling was 28+6 weeks. Parental counselling was performed four times (median), mostly by Pediatric Cardiologists (83.6%). Overall counselling was successful in 46.3%, satisfying in 51.9% and unsuccessful in 1.9%. Analyses of the analytical dimensions show that counselling was less successful for TOMK (38.3%) and PSC (39%); success rates were higher if additional written information or links to web sources were provided (60% and 70% respectively). Length of consultation was positively correlated to counselling success for ToMK (r=0,458), TrtTP (r=0.636), PSC (r=0.341) and TiMS (r=0.501). Interruptions were negatively correlated to the dimensions TiMS (r=-0.263) and TrtTP (r=-0.210). In presence of high-risk CHD (37.5%) overall counselling success was lower (26.1%). By cross table analysis and to a low degree of positive correlation in one dimension (ToMK; r=0.202), counselling tends to be less successful for ToMK, TrtTP and TiMS if parents have not been counselled by cardiologists. Analyses regarding premises show a parental need for a separate counselling room, which significantly impacts ToMK (r=-0,390) and overall counselling success (r=-0,333). A language barrier was associated with lower success rates for ToMK, TiMS and CR (21.4%, 42.9% and 30.8%). Conclusions Data from this multidisciplinary study indicate that parents after fetal diagnosis of CHD need uninterrupted counselling of adequate duration and quality in a separate counselling room. Providing additional written information or links to adequate web sources after initial counselling seem necessary. High-risk CHD needs more attention for counselling. There is a trend towards more counselling success if provided by cardiologists.